New species of Elateridae (Coleoptera) from Madre de Dios, Peru, with new taxonomic changes and distribution records - Johnson, Paul J. (2018)
The Elateridae fauna of Peru is updated with species new to science, new country records and new taxonomic combinations from the Madre de Dios region. Ten species representing eight genera are described as new: Conoderus wachiperi new species (Agrypninae, Oophorini) Cosmesus aca new species (Elaterinae, Pomachilini), Dipropus amarakaeri new species and Dipropus losamigos new species (Elaterinae, Ampedini, Dicrepidiina), Esthesopus machiguenga new species (Cardiophorinae), Glyphonyx peruanus new species (Elaterinae, Adrastini), Lissomus carmen new species (Lissominae), Paradonus kosnipata new species (Negastriinae), and Pomachilius qusqu new species and Pomachilius wayqecha new species (Elaterinae, Pomachilini). Aeolus platynotus Candèze is changed to Conoderus platynotus (Candèze) new combination and Aeolus ticuna Johnson is changed to Conoderus ticuna (Johnson) new combination (Agrypninae, Oophorini); and Crigmus brunnipilis (Candèze) is changed to Probothrium brunnipilis (Candèze) new combination (Elaterinae, Elaterini). Twenty-seven (27) species, the genera Glyphonyx Candèze and Paradonus Stibick, the tribe Adrastini, and the subfamily Negastriinae are added to the Peru faunal list. There are now 201 species representing 48 genera and 9 subfamilies recorded from Peru.